Inovasi Desain Produk Kuliner Berkelanjutan untuk Dekarbonisasi - Yusmaneli; Nabila (Design Journal, 2024)
In the realm of culinary design, sustainability has emerged as a critical imperative to mitigate environmental impacts, particularly carbon emissions. This research explores innovations in sustainable culinary product design aimed at decarbonization. Through a comprehensive literature review and case studies, the study identifies and evaluates various strategies and technologies employed to reduce carbon footprints in food production and distribution. The methodology involves analyzing current innovations and their effectiveness in achieving sustainable outcomes. The findings highlight key innovations such as eco-friendly packaging, efficient energy use, and sourcing practices that minimize environmental harm. By examining these innovations, the research contributes to understanding their potential for broader application in the culinary industry. This study underscores the significance of integrating sustainability into culinary product design to foster a more environmentally responsible food ecosystem